2021
DOI: 10.1186/s10195-021-00584-w
|View full text |Cite
|
Sign up to set email alerts
|

Do standards of care and early outcomes of periprosthetic fractures change during the COVID-19 pandemic? A multicentre study

Abstract: Background Periprosthetic fractures (PPFs) are a growing matter for orthopaedic surgeons, and patients with PPFs may represent a frail target in the case of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The purpose of this study is to investigate whether hospital reorganisations during the most severe phase of the SARS-CoV-2 pandemic affected standards of care and early outcomes of patients treated for PPFs in Northern Italy. Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hip replacements are generally the most common elective procedure, but elective procedures were halted and therefore most institutions did not perform them. Hip fractures have still been very common during this time[ 4 , 25 , 28 ]; however, the pandemic has increased the mortality and complication rate particularly amongst COVID-positive patients[ 5 , 8 , 11 , 16 , 38 ]. The importance of early treatment and proper rehabilitation was strongly emphasized in order to ensure prompt recovery[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip replacements are generally the most common elective procedure, but elective procedures were halted and therefore most institutions did not perform them. Hip fractures have still been very common during this time[ 4 , 25 , 28 ]; however, the pandemic has increased the mortality and complication rate particularly amongst COVID-positive patients[ 5 , 8 , 11 , 16 , 38 ]. The importance of early treatment and proper rehabilitation was strongly emphasized in order to ensure prompt recovery[ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zagra et al [ 16 ] conducted a retrospective multicenter study in patients with periprosthetic fractures (PPF) during COVID-19 pandemic in northern Italy. Out of 1390 patients, 38 were found to suffer from PPF.…”
Section: Clinical Presentationsmentioning
confidence: 99%
“…(24,27,61,62). On the other hand, health care providers preferred close observation and conservative management to surgery in patients with younger age and better overall health condition (31,63,64) So the majority of operations were performed on elder adults with multiple comorbidities and more critical conditions with poorer prognosis (24,33,34,46,52,65).…”
Section: Discussionmentioning
confidence: 99%
“…Dallari et al reported that few COVID-19-positive patients were surgically treated within 48 hours, and it seems that surgery performed within 48 hours does not associate with lower mortality in this subgroup of patients. However, according to the authors, these data could be influenced by the discrepancy of size between the COVID-19-positive and COVID-19-negative groups [ 23 ].…”
Section: Discussionmentioning
confidence: 99%